Practical Applications of Dispersely Reinforced Concrete with Polypropylene Fibers: Beams - Muntean, Radu; Cazacu, Christiana; Mizgan, Paraschiva; Galatanu, Teofil; Tamas, Florin (Elsevier BV, 2017)
The practical applications of dispersely reinforced concrete with polypropylene fibers are various; one of them may be achieving concrete beams reinforced by steel bars and dispersely spread polypropylene fibers. The paper presents some practical tests showing the combined effect of steel and fibers reinforcement over the bending load bearing capacity, the shear strength and deformations for concrete beams. The test results could represent a small contribution to the development of knowledge in the dispersely reinforced concrete aria using one type of polypropylene fibers, for which the information on their field of application is scarce or missing.